Financial Performance Affecting Stock Prices of Food and Beverage Sub-Sector Companies in Indonesia - Hedwigis Esti Riwayati; Permatasari Emanue , Magdalena (Management Research Studies Journal, 2024)
This research aimed to analyze the effect of return on asset, return on equity, debt to equity ratio and earning per share toward stock price in company food and beverage sub-sector listed on the Indonesia Stock Exchange during the period 2018 to 2022. The population in this research was 118 companies in the consumer non-cyclicals sector. The determination of samples is using purposive sampling method, so that the selected sample is relevant to the research objectives. The company sampled in this research was 16 food and beverage companies. Researchers used data panel regression analysis techniques with data processing using the E-views 10 application to test the research hypothesis. The results shows return on assets and return on equity has no positive effect on stock prices, debt to equity ratio has a negative effect on stock prices and earning per share has a positive effect on the stock price of food and beverage sub-sector companies. These research results are simultaneously shows that the return on asset, return on equity, debt to equity ratio and earning per share variables are capable to explain stock prices on those 16 food and beverages companies listed on the Indonesia Stock Exchange.